Lightweight Dual-Functional Segregated Nanocomposite Foams for Integrated Infrared Stealth and Absorption-Dominant Electromagnetic Interference Shielding - Ma, Zhonglei; Jiang, Ruochu; Jing, Jiayao; Kang, Songlei; Ma, Li; Zhang, Kefan; Li, Junxian; Zhang, Yu; Qin, Jianbin; Yun, Shuhuan; Zhang, Guangcheng (Nano-Micro Letters, 2024)
Lightweight infrared stealth and absorption-dominant electromagnetic interference (EMI) shielding materials are highly desirable in areas of aerospace, weapons, military and wearable electronics. Herein, lightweight and high-efficiency dual-functional segregated nanocomposite foams with microcellular structures are developed for integrated infrared stealth and absorption-dominant EMI shielding via the efficient and scalable supercritical CO2 (SC-CO2) foaming combined with hydrogen bonding assembly and compression molding strategy. The obtained lightweight segregated nanocomposite foams exhibit superior infrared stealth performances benefitting from the synergistic effect of highly effective thermal insulation and low infrared emissivity, and outstanding absorption-dominant EMI shielding performances attributed to the synchronous construction of microcellular structures and segregated structures. Particularly, the segregated nanocomposite foams present a large radiation temperature reduction of 70.2 °C at the object temperature of 100 °C, and a significantly improved EM wave absorptivity/reflectivity (A/R) ratio of 2.15 at an ultralow Ti3C2Tx content of 1.7 vol%. Moreover, the segregated nanocomposite foams exhibit outstanding working reliability and stability upon dynamic compression cycles. The results demonstrate that the lightweight and high-efficiency dual-functional segregated nanocomposite foams have excellent potentials for infrared stealth and absorption-dominant EMI shielding applications in aerospace, weapons, military and wearable electronics. Highlights: 1 Lightweight dual-functional segregated nanocomposite foams are developed via the supercritical CO2 (SC-CO2) foaming combined with hydrogen bonding assembly and compression molding strategy 2 The segregated nanocomposite foams exhibit superior infrared stealth performances benefitting from the synergistic effect of highly effective thermal insulation and low infrared emissivity. 3 Excellent absorption-dominant electromagnetic interference shielding performances are achieved owing to the synchronous construction of microcellular structures and segregated structures